Aso Environment & Sculpture International Symposium. (Aso Ikoi: Aso Ikoi Village, 1984)
Nakajima, Kazuo ; Honda, Takatomo ; Iwashita, Kyoko ; Nishimura, Fumio ; Suzuki, Toru ; Koga, Masaru ; Kawakami, Jun-ichi ; Irrgang, Rainer ; Fujibe, Yoshito ; Graham, Robert G.
Aso Environment & Sculpture International Symposium, Aso Ikoi Village, July 21 through September 11 1984. The Aso Environment and Sculpture International Symposium was organized to commemorate the 50th anniversary of the establishment of Aso National Park. Outdoor sculpture by Japanese and foreign artists was exhibited and related events were carried out to promote the Aso area. The purpose of the exhibition is to create a dynamic space where art is harmonized with nature.
boek